Building Reading Fondness Through Management Taman Bacaan Masyarakat (TBM) - Syur'aini, Syur'aini; Jamaris, Jamaris; Jalius, Jalius (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
Reading is the first obligation that God commands His people. Because by reading we can find out what is not yet known. Reading can sharpen thinking power and improve writing skills. Reading is not only explicit but also implied from all natural phenomena. So that reading activities run well, a place that can accommodate both reading and writing activities is needed. The place referred to in this paper is in the form of TBM. For the implementation of reading activities smoothly, it is necessary to manage the institution which includes planning, implementing, organizing, evaluating and developing. TBM not only functions as a place to read and write but also at the same time other activities that support reading activities, such as sports and arts activities, entertainment and recreation, so these activities need to be programmed at TBM.